Implementation of Deep Learning and the Development of Conceptual Understanding among Elementary School Students at SD Negeri 13 Kubu - Asmadi Asmadi; Agung Hartoyo Junaidi; Marinu Waruwu Junaidi; Mashudi Mashudi; Erlina Erlina (Attractive : Innovative Education Journal, 2025)
Deep learning in elementary education is often discussed in terms of student engagement and learning outcomes, while less is known about the pedagogical processes through which it supports conceptual understanding. This study examines how deep learning is implemented in elementary IPAS learning, identifies the processes through which students construct and refine conceptual understanding, and develops an empirically grounded conceptual model. A qualitative single-case study was conducted in a Grade 5 classroom at an elementary school in Kubu Raya, Indonesia. Data were collected through classroom observations, semi-structured interviews, and document analysis involving one teacher, 17 students, and one school principal. Data were analyzed through data condensation, data display, cross-source comparison, and conclusion drawing and verification. The analysis identified five interconnected pedagogical mechanisms: activation of prior knowledge, collaborative meaning-making, scaffolding and formative feedback, reflection on understanding, and contextual application. Mindful learning supported attention and cognitive readiness, meaningful learning functioned as the primary process of conceptual construction and refinement, while joyful learning provided conditions for sustained participation. These dimensions operated recursively rather than sequentially, through which students constructed, examined, revised, and applied emerging understanding. The study proposes a Systemic Deep Learning Model for Conceptual Understanding Formation, offering a process-oriented explanation of how deep learning may support conceptual development in elementary IPAS learning.